If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6+17x=-15+15x
We move all terms to the left:
6+17x-(-15+15x)=0
We add all the numbers together, and all the variables
17x-(15x-15)+6=0
We get rid of parentheses
17x-15x+15+6=0
We add all the numbers together, and all the variables
2x+21=0
We move all terms containing x to the left, all other terms to the right
2x=-21
x=-21/2
x=-10+1/2
| 3x-3+57=180 | | -12=3+3y | | -4+x/2=9 | | 4x+2x-6=90 | | 9x-14=47(2) | | 2x+4+16x20=180 | | 7/2+3x=20 | | 1/6(x-5)=-4 | | 4k²-36=0 | | 7/8t–24=25 | | 4u+36=12 | | 2x+4+16×20=180 | | 4×-2y=7 | | 29+112+x=180 | | x-7.4=11.2 | | y=-14(7+5) | | Y=-16t^2+40 | | (4x+3)(x-5)=4x^2-15 | | x*(x+16)=225 | | h-26=-2 | | 9=3s-3 | | x/4−9=−2 | | n+3=5n-12 | | 12.5x+4=7x*37 | | 280=6x5x | | y=-11+3(12) | | -4(10+7x)=-264 | | 1-6x-7x=27 | | 0.3x+1.2=4.5 | | 5(9+3x)=195 | | 2(y-5)-6y=26 | | 14x^2+12x-6=-6 |